IMPLEMENTATION OF RECYCLING-BASED ENVIRONMENTAL EDUCATION IN BUILDING AWARENESS OF FLOOD DISASTER RESILIENCE IN STUDENTS OF SDN 3 KENANGA - Hesti Muliawati; Siti Karimah; Gina Nurfaidah; Rahma Maulida; M. Fauzan Ardiansyah (Ann Publisher, 2026)
Aims. This study aims to describe the implementation of recycling-based environmental education in fostering flood disaster resilience awareness among elementary school students. The program was conducted as a community service activity through the Kuliah Kerja Nyata (KKN) at SDN 3 Kenanga Village, Cirebon Regency, involving fifth-grade students as participants. Methods. This study employed a descriptive qualitative approach, with data collected through observation, questionnaires, and documentation. The educational program was designed in three stages: introduction (providing materials on waste, floods, and the 3R concept); implementation (hands-on recycling activities that transform used gallons into plant pots and trash bins using a STEAM approach); and sustainability action (utilizing students' products in school facilities). Result. The findings indicate that the program effectively improved students' understanding of the relationship between waste management and flood risk, as reflected in questionnaire responses and active participation. In addition, positive behavioral changes were observed, such as increased adherence to proper waste disposal and a growing awareness of the need to remind peers to maintain cleanliness. Conclusion. The recycling activities also enhanced students' creativity and sense of environmental responsibility. Therefore, participatory and experiential recycling-based environmental education proves to be an effective strategy for building early flood-disaster resilience awareness. This program has the potential to be developed as a sustainable model for environmental and disaster education at the elementary school level.